Charalambous, Andreas - (:unkn) unknown (My University, 2026)
Andreas Charalambous, BSc, MSc, PGCert (Research), PhD (Oncology Nursing), started his nursing career in 1995. He obtained his BSc in Nursing Science in 1999 by the Northumbria University (U.K), his MSc (Nursing Science) in 2002 and his PhD (Oncology Nursing) in 2008 from Middlesex University (UK). He has a proven track in academia since 2004. Ηe is the Chair of the Nursing Department at the Cyprus University of Technology where he works as an Associate Professor of Oncology and Palliative Care and he also holds the position of an Adjunct Professor at University of Turku (Finland). He is the founder and Past-President of the Cyprus Oncology Nursing Society, European Oncology Nursing Society (EONS) Past-President and European Cancer Organization President-Elect. He is also the Founder of the Cancer Nursing Fund (https://cancernurse.eu/cancer-nursing-fund/). He is involved in National and International research programs (HORIZON2020, ERASMUS+, COST) in various fields of cancer care. Examples of externally funded projects include: PI in the ERASMUS+ project PROLEPSIS (https://prolepsis.eu/) and PI (Cyprus team) in the ERAMUS+ project HERO (https://hero-erasmus.csl.gr/), PI (Cyprus team) in the HORIZON project INCISIVE (https://incisive-project.eu/) He has published over 150 National and International publications in esteem journals. H-index 29 and i10-index 56 https://scholar.google.com/citations?hl=en&user=P13f8NsAAAAJ
Keywords: Supportive Care; Oncology; Digital Health; Translational Research; nursing